UNFSS Science Days Side Event: COVID-19, food systems, and One Health in an urbanizing world: Research responses at a national level - Veenhuizen, René van (2021)
Rene van Veenhuizen POLICY SEMINAR UNFSS Science Days Side Event: COVID-19, food systems, and One Health in an urbanizing world: Research responses at a national level Co-Organized by CGIAR and RUAF JUL 6, 2021 - 09:30 AM TO 11:00 AM EDT